Applications of Image-Guided Navigation in the Middle Cranial Fossa: An Anatomic Study - Bumpous, Jeffrey M. (1996)
Determining the location of pertinent anatomic structures (ie, the internal auditory canal [IAC]) in middle cranial fossa surgery is commonly based on indirect inferences from bony landmarks. Several methods have been proposed for identification of the IAC, each using bony landmarks coupled with geometric formulation. Identification of the IAC based on bony architecture and geometry may be severely limited when a mass lesion is present. Image-guided surgery has the advantage of rapid localization and may be helpful in navigating a complex surgical field which has been distorted by tumor. This study evaluates the feasibility and accuracy of the ISG viewing wand in determining pertinent anatomic landmarks in the middle fossa of the human cadaver. High-resolution (1 mm) computed tomography was performed on a preserved human cadaver head in which fixed fiducial markers had been placed. Subsequently, the cadaver head was registered in a simulated operative field, and middle fossa craniotomy was performed. The foramen spinosum, foramen ovale, greater superficial petrosal nerve, internal carotid artery, arcuate eminence, and IAC were identified visually, and three independent localizations of each structure were performed with the viewing wand. Accurate localizations were consistently performed within 1 mm for each anatomic landmark. Image-guided navigation is both feasible and accurate in determining intraoperative landmarks in the middle fossa. Image-guidance may enhance surgical accuracy and efficiency. Further clinical studies evaluating image-guided techniques in the middle fossa are warranted.